Experiencia de la incorporación del aprendizaje colaborativo, doblado de papel y TICs en la enseñanza de las secciones cónicas - Alvarado Alvarado, Alejandra (2019)
One of the main challenges of education is to ensure that students construct knowledge in an significative way and that their training does not consist of an application of formulas for the resolution of exercises. We propose a strategy based on collaborative learning for the teaching of the Conic Sections at the initial university level. The application carried out in an Intermediate Calculus course includes the manipulation of mathematical objects through paper and the use of Information and Communication Technologies (ICTs) to generate conjectures, verify properties, deduce equations, solve problems and study Applications. The implemented strategy showed positive results and high satisfaction of the students, who worked in groups and plays a protagonic role during the various activities and that allowed to construct concepts from the simple to the complex.